“Ah, it's best not to mention that here:” Experiences of LGBTQ+ health professionals in (heteronormative) workplaces in Canada - Bizzeth, Stephanie R.; Beagan, Brenda L. (Frontiers in Sociology, 2023)
Introduction Despite human rights protections for lesbian, gay, bisexual, transgender, and queer (LGBTQ+) people, LGBTQ+ professionals may continue to experience discrimination working in heteronormative systems and spaces. Methods In this qualitative study 13 health professionals (nurses, occupational therapists, and physicians) from across Canada participated in in-depth qualitative interviews to explore their experiences with work-related microaggressions and heteronormativity. Results Heterosexist microaggressions from both patients/clients and colleagues were the norm, perpetuating and bolstered by heteronormative workplace and professional cultures. In turn, LGBTQ+ professionals navigated disclosure-decision-making, in power-laden contexts where all options carried potential negative consequences. Discussion Drawing on the notion of “heteroprofessionalism,” we argue that the concept of professional carries encoded within it demands that the occupant of that category be—or present as—heterosexual, an unmarked status that can be readily desexualized. Acknowledging sex and sexuality disrupts “professionalism.” We argue that such disruption, indeed dissention, is necessary to open (hetero)professional spaces to LGBTQ+ workers.